TGF-β3-mediated phagocytosis protects mammary epithelial cells of ketotic dairy cows against metabolic stress–induced inflammatory damage - Chang, Renxu; Jia, Hongdou; Chen, Yuanyuan; Loor, Juan J.; Xu, Qiushi; Ma, Li; Li, Ming; Shen, Taiyu; Li, Xiaobing; Xu, Chuang; Sun, Xudong (Journal of dairy science, 2025)
The supraphysiological levels of free fatty acids (FFA) during early lactation led to an inflammatory response in the mammary gland of ketotic cows, which may be attributed to the untimely clearance of apoptotic cells (AC). Given the engulfment role of mammary epithelial cells for AC and the regulation of TGF-β3 on phagocytosis, we speculated that TGF-β3-mediated phagocytic function is closely related to inflammatory response in the mammary gland of ketotic cows. The objective of this study was to elucidate (1) the inflammatory state and phagocytic function of mammary epithelial cells and activity of the TGF-β3 pathway in mammary gland of ketotic cows, and (2) the role of TGF-β3-mediated phagocytosis on the inflammatory response of bovine mammary epithelial cells in response to exogenous FFA. In this study, excessive proliferation of AC, NF-κB/MAPK-mediated inflammatory response, TLR4-mediated local natural immune dysfunction, phagocytic dysfunction of mammary epithelial cells, and activation of the TGF-β3 pathway were detected in the mammary gland of ketotic cows or in immortalized bovine mammary epithelial (MAC-T) cells in response to exogenous FFA. Knockdown of TLR4 attenuated the FFA-induced inflammatory response in MAC-T cells. Overexpression of TGF-β3 exacerbated FFA-induced TLR4-mediated local immune dysfunction and inflammatory response by aggravating phagocytic responses. Knockdown of TGF-β3 attenuated the overactivation of inflammation resulting from FFA challenge through inhibition of the TLR4 pathway, which improved phagocytic ability in MAC-T cells. Taken together, TGF-β3-mediated phagocytosis may be a promising therapeutic target for reducing the negative effect of FFA-induced inflammation in mammary gland of dairy cows with ketosis.